Territorial intelligence and social milk. Neglected peoples of Latin America : Proposal for Mercosur - Bozzano, Horacio (2010)
By applying the concepts of understanding, intelligence and territorial development, this publication offers a program proposal "Social Milk in MERCOSUR", carries great social replicability, notable territorial diffusion, institutionalization strong degree of public and scientific support and technical. "Social Milk" aims -with other projects TAG Territorios Posibles- pull one way to construct another form of development in Latin America.